Structure of the rat osteocalcin gene and regulation of vitamin D-dependent expression. - Lian, J (1989)
The osteocalcin gene encodes a 6-kDa polypeptide, which represents one of the most abundant noncollagenous bone proteins, and the present studies establish that osteocalcin mRNA is detected only in bone tissue. An osteocalcin gene was isolated from a rat genomic DNA library, and sequence analysis indicated that the mRNA is represented in a 953-nucleotide segment of DNA consisting of four exons and three introns. A modular organization of the 5' flanking sequences of the gene is reflected by the presence of at least three classes of regulatory elements, which include the following: (i) RNA polymerase II canonical sequences; (ii) a series of consensus sequences for hormone receptor binding sites and cyclic nucleotide responsive elements consistent with physiologic expression of the osteocalcin gene; and (iii) a 24-nucleotide sequence in the proximal promoter region with a CAAT motif as a central element. We have designated this highly conserved sequence as an "osteocalcin box" since only 2 nucleotide substitutions are found in the rat and human osteocalcin genes. We have demonstrated two factors regulating osteocalcin gene expression. First, a 200-fold increase occurs in normal fetal calvaria osteoblasts producing a mineralizing matrix, compared to confluent osteoblasts in a nonmineralizing matrix. Second, contained within the 600 nucleotides immediately upstream from the transcription start site are sequences that support a 10-fold stimulated transcription of the gene by 1,25-dihydroxyvitamin D.